Examining the trends of research on educators’ readiness in online teaching & learning (2013-2022): a bibliometric analysis - Ghazali, Norliza; Mustakim, Siti Salina; Yap, Bee Wah; Mohd Nasir, Farah Damia; Azmar, Khairunisa (Institute of Advanced Engineering and Science (I A E S), 2024)
Despite recent emphasis, the usage of online and blended learning as instructional methodologies in higher education is still unequal, leading to variations in students’ learning experiences across structures, areas, and programs. Research on the aspects concerning educators’ adoption and adaptation of online teaching is crucial to overcome this limitation. By using the terms ‘Educators AND Online Learning AND Readiness’, 391 journal articles were listed for further analysis. Microsoft Excel was used for frequency analysis, VOSviewer to visualize data, Harzing’s Publish or Perish to compute and evaluate citation metrics, and Words Cloud to create a cluster of words that were shown in various sizes. The bibliometric criteria used in this study to summarize results includes language, topic area, research trends by year of publication, top contributors by nation, most significant institution, and name of the active source and others. This research includes a citation analysis, an authorship analysis, and keyword analysis. The results show that from 2013 to 2022, the rate of publication increased, and a spike was seen from 2019 to 2020 due to the COVID-19 epidemic. Identification of the important blended learning outcome predictors will help with the initial planning of this creative pedagogical strategy.